Munčev okarček, Coenonympha tullia (Müller, 1764) (Lepidoptera: Nymphalidae) v Sloveniji ni izumrl - Čelik, Tatjana (Acta entomologica slovenica (Ljubljana), 2012)
The threatened and protected Large Heath butterfly, Coenonympha tullia (Müller, 1764) (Lepidoptera: Nymphalidae), was rediscovered 10 years after its last record in Slovenia. Between 1962, when it was first observed in Slovenia, to 2001 (last observation), only six localities were known. In the red list of Slovenian Lepidoptera it is classified as an endangered species (E) and in the recent years it has been considered as presumably extinct in Slovenia. The main aim here is to report on the habitat, population status and threats of the currently only known population of this species in Slovenia, now known to inhabit the Natural Reserve Zelenci near Kranjska Gora. Due to such specific status of the species in the Slovenian butterfly fauna, I also provide a review of its historical distribution in Slovenia along with the information about its global distribution, life history and ecology.
Keywords: Coenonympha tullia; dejavniki ogrožanja; distribution; habitat; Lepidoptera; metulji; munčev okarček; population status; prevalence; razširjenost; Slovenia; stanje populacije; threats; Zelenci